SINGLE VERSUS 3-DOSE ANTIBIOTIC PROPHYLAXIS IN CLEAN AND CLEAN CONTAMINATED OPERATIONS - Surahio, Abdul Rashid; Khan, Ashar Ahmad; Farooq, Main Usman; Fatima, Iffat (Journal of Ayub Medical College Abbottabad, 2010)
Background: Infection is a great problem in surgery and is encountered by all surgeons by nature of their craft; they invariably impair the first line of host defence. Bacteria may enter the wound during or after the operation and may be of endogenous or exogenous origin. The objective of this study was to determine the effectiveness of preoperative antibiotic prophylaxis in reduction of postoperative wound infection in clean and clean contaminated procedures and to compare the cost of antibiotic prophylaxis in both groups. Method: This was a prospective study done on patients in General Surgery Department, Al-Noor Specialist Hospital, Holly Makkah, Saudi Arabia from 1st April 2006 to 30th March 2007. Total 400 patients were divided into 2 groups of 200 patients each: Group-A received single dose antibiotic prophylaxis, and Group-B received 3 doses of antibiotic therapy. Only clean and clean contaminated procedures were included and results were compared. Results: In Group A, clean procedures (Group-A1) were 110, and clean contaminated (Group-A2) were 90 patients. In clean procedure, rate of infection was 5 out of 110 (4.54%) and in clean contaminated procedures it was 3 out of 90 (3.33%). In Group B, in clean procedures (Group-B1), rate of infection was 7 out of 90 (7.77%), while in clean contaminated procedures (Group-B2) it was 9 out of 110 (8.18%) patients. Over all wound infection rate after single dose antibiotic prophylaxis was 4% in both procedures and 8% after 3- dose antibiotic therapy. Conclusion: Single dose antibiotic prophylaxis is as effective as 3-dose therapy in clean and clean contaminated procedures to prevent wound infection and is cost-effective. Keywords: Surgical wound, Infection, Antibiotic prophylaxis, Clean, Clean contaminated procedure